College Student Lay Health Information Mediary Behavior: an Examination of eHealth Literacy and Unrequested Health Advice - (:unkn) unknown (My University, 2014)
Lay health information mediary behavior (LHIMB) describes individuals seeking health information to relay to others. The current study examines LHIMB as a relationship between eHealth literacy and unrequested health advice (UHA). 254 undergraduate students completed a survey addressing eHealth literacy levels, general UHA behaviors and specific UHA episodes. Results on general UHA behaviors indicate no significant relationship exists between eHealth literacy and utilizing UHA in health decision-making or frequency of offering UHA. However, self-perceived health status and degree of health worry significantly predict using UHA in health decision-making. Further, as health worry increases, participants appear significantly more likely to receive and offer UHA. Results on specific UHA episodes suggest the majority of UHA occurs within close relationships. Rather than utilizing Internet sources, the majority of UHA employs personal experience as the primary health information source. Though the quality and reliability of online health information may not presently represent a significant concern to college student health, future research should further examine the observed partiality shown toward personal experience and student reliance on lay health sources demonstrated in the current study.
Keywords: College Students; eHealth Literacy; Health Mediaries; Social Support; Unrequested Advice